(3efgL GdWdGH aj Gdabgs - (3RcQjG Hf eMeO Hf CMeO Hf RcQjG GdCfUGQj GdSfjcj GdeUQj GdTGaYqj, CHh jMji , J (B926 (3g` s; (3Gdfhhj,J (B676 (3g` s ((3eMeO Hf YHO Gddg GdbjGfi GdZeQi GdZeQGfi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi gOGfG dgPG hHYO agPG eNJUQ ai Gdabg Ydi ePgH GdEeGe GdTGaYi ENJUQJ ajI eNJUQ GdEeGe CHj RcQjG Gdfhhi GdeSei HefgGL GdWGdHfj hVeeJ Edjg eG jSQ hSejJg HefgL GdWdGH s
(3BNQgG (B:s
(3hdG jUM JedcgG ef ZjQgG hhgfG chdOgG GdJGHY dgG , hYJbgG ef QCS GdeGd , hGddg CYde s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHI s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
Keywords: (3Gdabg GdESdGejs